Law Enforcement Against Liquor Distribution by Police in The District of Demak - Misbakhul Munir; Sri Endah Wahyuningsih (Jurnal Daulat Hukum, 2018)
Issues examined in this study were (1) Implementation of law enforcement against liquor by the Police Demak. (2) Obstacles encountered. (3) How the solutions do about it. The purpose of this study was to understand, describe, analyze and assess the implementation of enforcement by the Police in combating liquor Demak. The method used is Juridical Sociological with specification of descriptive analysis, the data used are primary data and secondary data so that the data collection method used is qualitative analysis. (1). Implementation of Law Enforcement by Police in combating liquor Demak carried out by (a) Preventive measures, namely the dissemination and raids (b) repressive actions, namely investigation, investigation, prosecution and trial. (2). Barriers Police Demak in law enforcement in combating the circulation of liquor (a) factor is the law that is not yet the enactment of a special law regulating the circulation of liquor (b) Factors law enforcement, namely the limited human resources (c) Factors of facilities (d) community factors, namely the lack of legal awareness (e) Cultural factors of society violates the cultural values of society. (3) Efforts by the Police Demak to overcome the obstacles in the fight against the circulation of liquor (a) Factors law (b) Improve the quality of Human Resources (c) Adding equipment and funds (d) Conducting socialization (e) To promote cooperation between agencies Related in Demak district.Keywords: Law Enforcement, Police, Liquors.